Tourism as an opportunity to effectively counteract marginalisation. The case of the Italian national strategy for inner areas - Cotella, Giancarlo; Vitale Brovarone, Elisabetta (European Spatial Research and Policy, 2023)
Remote rural areas are often rich in natural and landscape assets, which are in turn used as the main focus of tourism development strategies aiming at reverting their decline. However, mono-functional strategies hardly manage to achieve this goal, as in order to restore those structural conditions that are essential to liveability and local development it is necessary to engage in a more comprehensive approach. Acknowledging this challenge, the paper reflects on the possibility to include tourism within multi-level development strategies aimed at tackling marginalisation, drawing on the case of the Italian National Strategy for Inner Areas. More in detail, the authors analyse how the latter enables the integration of tourism-related actions into more comprehensive, place-based development strategies that act upon the peculiarities of the territories they focus on through a mix of top-down and bottom-up logics.